Resolving taxonomic and nomenclatural problems in the genus Caligus O.F. Müller, 1785 (Copepoda: Caligidae). - Boxshall, G.A. & J.P. Bernot (Zootaxa, 2023)
Supplementary descriptions are provided for six poorly known species of Caligus, based on a study of type and other material carried out by the late Roger F. Cressey but never published. As part of that study new illustrations were produced by Hillary Boyle Cressey who has kindly made these previously unpublished drawings available to this paper. The present account also contains critical re-assessments of the validity of several other species of Caligus Müller, 1785. It is proposed to recognise that: C. glacialis Gadd, 1910 and C. raniceps Heegaard, 1943 are junior subjective synonyms of the type species C. curtus Müller, 1785 and we consider the published geographical locality given for C. raniceps by Heegaard (1943) to be erroneous; C. guerini Guiart, 1913 is a junior subjective synonym of C. elongatus von Nordmann, 1832; C. mordax Leigh-Sharpe, 1934 is a junior subjective synonym of C. coryphaenae Steenstrup & Lütken, 1861; C. lessonius Risso, 1826 is not a caligid and is probably a junior synonym of the pandarid Demoleus heptapus (Otto, 1821); C. clavatus Kirtisinghe, 1964 is a junior subjective synonym of C. sphyraeni Pillai, 1963; C. rotundigenitalis Yü, 1933 is a junior subjective synonym of C. torpedinis Heller, 1865; C. hyalinae Heegaard, 1966 is a junior subjective synonym of C. chelifer Wilson, 1905; C. biseriodentatus, Shen, 1957 is a junior subjective synonym of C. pauliani Nuñes-Ruivo & Fourmanoir, 1956; and C. cornutus Heegaard, 1962 can be formally treated as a junior subjective synonym of C. lobodes (Wilson, 1911) because the name C. cornutus belongs with the male holotype; the female allotype collected by Heegaard (1962) remains unidentified. We also conclude that C. mebachii Marukawa, 1927 was based on a young male of Euryphorus brachypterus (Gerstaecker, 1853) and a male of Caligus coryphaenae Steenstrup & Lütken, 1861 which was mistakenly identified as the female. A lectotype is designated for C. mebachii and this species is treated as a synonym of Euryphorus brachypterus. It is noted that C. hamatus Heegaard, 1955 is conspecific with, and has priority over, C. undulatus Shen & Li, 1959. However, given that C. undulatus is a high profile and well known species, frequently recorded from across the Pacific, Indian and Atlantic oceans, a case has been submitted to the ICZN to grant precedence of C. undulatus over C. hamatus. We reject the transfer of Chalimus tenuis Leidy, 1889 to Caligus by Fowler (1912) on the basis of lack of evidence supporting the transfer, and return it to Chalimus, where it can be treated as a species inquirendum within a genus that is no longer considered as valid. We consider that C. alalongae Krøyer, 1863 and C. gracilis Dana, 1852 are species inquirenda. Caligus truttae is a nomen nudum because Giard (1890) provided no morphological information or illustration associated with the new name. Key words: nomenclature, redescriptions, new synonyms, sea lice